A new species of Sarcophaga (Pandelleisca) (Diptera, Sarcophagidae) from Turkey - Gamze Pekbey (ZooKeys, 2020)
A new species, Sarcophaga (Pandelleisca) mersinensis sp. nov. is described from the Mediterranean region of Turkey. The male terminalia are documented with line drawings, photographs and scanning electron microscope images. The species is compared with the two most similar species, Sarcophaga (Pandelleisca) baudeti (Lehrer) and Sarcophaga (Pandelleisca) theodori (Lehrer), both known from Israel. A key is provided to the western Palaearctic species of Pandelleisca Rohdendorf.